Hybrid Soybean as Green Manure for Improving Soil Properties and Subsequent Crop Growth - Haibo Qi; Bangrui Li; Junmei Fan; Wei Zhao; Yiming Ma; Yuan Suo; Mingjiu Wang; Yong Wang (Agronomy)
The rapid increase in fertilizer use has led to the degradation of soil quality, nutrient imbalances, reduced biodiversity, and soil compaction. To address these challenges, hybrid soybeans with efficient biological nitrogen fixation capabilities and broad environmental adaptability were selected as green manure to reduce fertilizer application, thereby improving soil fertility and structure. This study utilized the varieties “Forage Soybean S001” (S001), “Neinong S002 Forage Soybean” (S002), “Mengnong S003 Forage Soybean” (S003), “Mengnong S004 Forage Soybean” (S004), “Mengnong S005 Forage Soybean” (S005), and “Mengnong S006 Forage Soybean” (S006) as green manure materials. The clean tillage (CK) treatment served as the control, ensuring a residue-free soil surface while maintaining consistent practices in soil preparation, irrigation, and field management across all treatments. Field planting of green manure and subsequent crops was conducted at the M-Grass Ecology and Environment (Group) Company’s experimental site in Hohhot in early May of 2023 and 2024. The plots each measured 20 m2, with three replications arranged in a randomized block design. A combination of field experiments and laboratory analyses was utilized to investigate the effects of incorporating various hybrid soybean varieties as green manure on soil nutrient levels, soil enzyme activity, soil microbial communities, and the subsequent growth of oats. The results indicated that incorporating various hybrid soybean varieties as green manure into the soil significantly improved soil nutrient levels and enzyme activity. The diversity and richness of soil bacterial communities increased significantly, accompanied by alterations in community structure and composition. These changes enhanced soil fertility and optimized the microbial community structure, promoting the growth of subsequent crops. Among all the treatments, S001 and S004 were particularly effective in enhancing the soil environment, indicating their potential as superior green manure resources for broader application.